A combined MCDA – Monte Carlo simulation approach for the evaluation of investment decisions on public transit. (2017) - Roukouni, Anastasia; Vavatsikos, Athanasios P.; Giannopoulou, Maria; Medda, Francesca
As cities worldwide are projected to experience a noteworthy growth in population in the decades to come, additional strain is placed on many urban systems that are already at capacity. At the same time, public funds dedicated to transportation are experiencing vital cuts, creating this way considerable problems and forcing transportation specialists to investigate new ways of meeting this financial challenge; a set of options comes under the umbrella term 'value capture'. In this context, the objective of the present paper is to develop a multicriteria decision analysis (MCDA) evaluation framework for the selection of the most efficient value capture financing mechanism for urban investment on transportation infrastructure and more importantly, to conduct a comprehensive sensitivity analysis in order to examine the stability and thus efficiency of the obtained results. The MCDA method used is the analytical hierarchy process (AHP), while for the sensitivity analysis Monte Carlo simulation is used. The application of Monte Carlo simulation revealed very interesting pathways concerning the level of ambiguity and uncertainty of the results.